Porto-Splenic veins thrombosis and Budd-Chiari syndrome in a patient with essential thrombocythemia - is it always the myeloproliferative neoplasm to blame? - Suriu Celia; Braester Andrei; Barhoum Masad (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2021)
Essential Thrombocythemia (ET) is one of seven Myeloproliferative Neoplasms (MPNs), according to the latest WHO classification [1].